Surgical Education in the Internet Era - Pugh, Carla M., M.D., Ph.D; Watson, Andrew, M.D; Bell, Richard H., M.D; Brasel, Karen J., M.D., M.P.H; Jackson, Gretchen Purcell, M.D., Ph.D; Weber, Sharon M., M.D; Kao, Lillian S., M.D., M.S (The Journal of surgical research, 2009)
Technological advancements, along with economic and political issues, have resulted in major changes in surgical education. The development of high fidelity simulators and the widespread availability of the Internet have allowed learning to be shifted away from the operating room. Furthermore, the Internet provides an opportunity for surgical educators to standardize general surgery training and assessment and to develop collaborations nationally and globally. This paper highlights presentations about the challenges as well as the rewards of surgical education in the age of the Internet from the 2009 Academic Surgical Congress.